Advancing New Testament interpretation through spatio-temporal analysis : Demonstrated by case studies - Bakker, H. (2020)
This article explores, via three case studies, how spatio-temporal analysis can advance New Testament text interpretation. Case study 1 applies network analysis to data representing the Roman road network constrained by parameters valid for ancient times. Case study 2 located geographical entities from the text in a cartographic visualization and provided supportive information to compare contemporary textual resources. For the disciplines of textual and conjectural criticism (case study 3), spatio-temporal analysis opens a new window to study what would be the most probable variant of the original text.